Dynamics of the COVID-19 Epidemic Process and other Acute Respiratory Viral Infection in the Russian Far East (2019–2023) - A. A. Yakovlev; A. V. Shafigullin; A. F. Popov; M. Yu. Shchelkanov (Эпидемиология и вакцинопрофилактика, 2025)
Relevance. In the modern period, there are more and more publications showing that the COVID-19 pandemic has significantly affected the epidemiological situation with regard to a wide variety of infections, and having a different transmission mechanism. At the same time, ambiguous opinions are expressed about the causes of this phenomenon. Therefore, it is important to understand to what extent the reduction in morbidity is associated with the introduction of quarantine measures, or whether the mechanisms of competition between various infectious agents are important at the population level.Aims. To assess the dynamics of the epidemic process (EP) of COVID-19, influenza and acute respiratory viral infections in the population of different subjects of the Far Eastern Federal District in the period from 2019 to 2023. substantiating the hypothesis about the causes (factors) that influenced it. Materials and methods. The material for the study was data on morbidity taken from state reports "On the state of sanitary and epidemiological welfare of the population" for the subjects of the Far Eastern Federal District and in the Russian Federation, and Internet sources for 2019 – 2023. The main method was a retrospective epidemiological analysis of morbidity, using an integration approach (Pozdeeva E.S., Yakovlev A.A., 2012), which allows us to identify possible interactions between microorganisms. For ease of perception and the ability to present several curves in one figure at once, in this work, the incidence is calculated in terms of visibility, on the basis of which graphs are constructed reflecting the dynamics of the incidence of the infections in question.Results. The assessment of the dynamics of the incidence of SARS, influenza and COVID-19 in the Far Eastern Federal District did not reveal cardinal features in the dynamics of these infections in different administrative territories, which indicates the predominant influence of globally acting factors on the epidemic process. This probability reflects the theoretical views of Schmalhausen I.I. (1968), Yakovleva A.A. et al. (2018), that the biogeocenosis (global factor) acts as the controlling device in relation to all its constituent populations of species. Its self-adjustment forms the basis for the adaptability of species to their habitat and their mutual adaptation to each other. Therefore, changes in one parasitic system can also affect the parasitic systems of other infections, which are interconnected by integration and competitive relationships. This is reflected in the various manifestations of the epidemic process in different groups of infections.Conclusions. Trends in the dynamics of the incidence of COVID-19, influenza and other acute respiratory infections in most administrative territories of the Far Eastern Federal District in the period 2019–2023, as well as in the region of the Far Eastern Federal District and the Russian Federation as a whole, do not have cardinal features. this indicates the predominant influence of a globally active factor on the epidemic processes of these infections. The hypothesis is substantiated, according to which the realization of this factor is a consequence of the processes of self-adjustment of biogeocenosis.